Maximizing the Outreach of Microfinance in Nepal : The Case for a Central Technology Platform - World Bank (Washington, DC, 2014)
This report addresses the establishment of a centralized information and communication technology (ICT) platform for the microfinance sector in Nepal. It has been shown from international experience that ICT improves the efficiency, transparency, and outreach of microfinance institutions (MFIs) and reduces operational costs. There is an opportunity in Nepal to implement similar solutions, and this report provides information on these solutions and offers recommendations for implementing them in Nepal. The microfinance sector in Nepal has many players, but these players have shown few real successes. The sector is largely unsustainable, subsidy driven, and fragmented to the extent that it might not meet the real needs of the country. This report presents a new paradigm for introducing ICT in the microfinance sector of Nepal. The centralized technology platform was chosen as opposed to telecom-led platforms due to its ability to resolve most of the pertinent challenges that Nepal's microfinance sector faces. The paradigm can help remove most of the constraints that have limited the growth of MFIs and kept them from becoming sustainable, moving out to remote and rural areas, and providing more loans to those that need them. In the traditional paradigm, MFIs acquire ICT in an ad hoc fashion and are able to use it only partially to automate their operations.